Productive Zakat Fund Strategy Towards Economic Empowerment (Case Study At Baznas Oku District) - Mahatir Fathoni; Amie Amelila (International Journal of Economics, Business and Innovation Research, 2025)
The National Zakat Agency (BAZNAS) of OKU Regency is an institution that collects, manages and distributes zakat. One of the weaknesses of this institution is the practice that is still less than optimal and the very minimal impact felt by the underprivileged community. So that the number of poor people is getting higher, and there is a system that is less organized and orderly in the distribution of zakat, infaq and alms. The solution and way out is to foster the spirit of OKU Muslims to entrust their zakat to BAZNAS OKU. The target of this institution is to provide assistance to the underprivileged and deserving of zakat to meet their needs or provide capital for businesses that the person wants to start. However, it is not uncommon to find that the management of BAZNAS is not as it should be and is detrimental to many people, due to inappropriate and inappropriate practices. This study intends to analyze how to collect, manage, and empower productive zakat through BAZNAS with a new system and innovation, so as to get differences between the previous and current methods. In this study, the method used is qualitative research by collecting several data based on references from journals and reports from the BAZNAZ OKU institution. The results of this study indicate that the collection of productive zakat at BAZNAS OKU has fluctuated in the last three years, 2022-2024, corporate zakat is the main source of zakat funds, while individual zakat is still very low, the zakat management system still faces challenges in transparency and distribution effectiveness, there are weaknesses in the data collection of mustahik and the distribution of zakat evenly, minimal innovation in the use of digital technology to support the zakat management system, productive zakat is partly used to provide business capital to mustahik. However, the number of zakat recipients from the poor is still low compared to the number of poor people in OKU, lack of training programs and business assistance for mustahik who receive productive zakat